Field notes contributed by Dean Mosman, fall 1982 - Mosman, Deanet al (1982)
Field notes were contributed by Dean Mosman. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1982. Epson - sheet feed